English Language Learning Strategies to Improve the Language Skills of Elementary School Students - Siregar, Tiarnita Maria Sarjani Br.; Ilmy, Wahyu Nurul; Pos, Maymunah Pos; Rayhan, Nayla Arifa; Lestari, Putri Ayu (International Journal Of Education, Social Studies, And Management (IJESSM), 2026)
English language learning in primary schools plays an important role in building students' language skills from an early age. However, in practice, English language learning still faces various challenges, such as low student motivation, limited learning strategies, and a lack of media that is appropriate for primary school students. This study aims to examine various effective English learning strategies in improving the language skills of primary school students. The research method used is a literature study by reviewing SINTA indexed national journal articles and reputable international journals relevant to the research topic. The data were analysed using qualitative descriptive analysis techniques by grouping and synthesising previous research findings. The results of the study show that the application of interactive and communicative learning strategies, such as the Audio Lingual Method, Total Physical Response (TPR), cooperative learning, and the use of visual and audiovisual media, can increase the motivation, participation, and language skills of primary school students. Thus, the application of varied English learning strategies that are appropriate for the characteristics of primary school students is necessary to create effective and meaningful learning.